The economics of ESG disclosure regulation - Frankel, Richard; Kothari, S. P.; Raghunandan, Aneesh (Review of Accounting Studies, 2025)
Abstract We provide an economics-based review of the pros and cons of ESG disclosures, emphasizing environmental disclosures from an investor-centric perspective. Our survey intends to guide corporate management and regulators in navigating the ESG disclosure terrain. Rather than summarizing the vast and growing ESG literature, we assess the economic arguments for ESG disclosure regulation and the form of this disclosure. We discuss investors’ demand for ESG information and its supply by publicly traded firms. We analyze the case for and against mandatory ESG disclosure. Finally, we weigh the efficiency of disclosure requirement characteristics, assuming mandatory ESG disclosure is warranted. We intend to be positive rather than prescriptive, providing a line of reasoning readers can employ to reach their own conclusions about what we ought to do.